Household indebtedness and well-being: Evidence from Australia - Maram Tammam; Khaled Toffaha; Michael A. Kortt; Albert Wijeweera (PLoS ONE, 2025)
This study examines the relationship between household debt and health among Australian adults aged 18-65, utilising five waves of the Household, Income and Labour Dynamics in Australia (HILDA) Survey (2006, 2010, 2014, 2018, and 2022). The analysis distinguishes between unsecured credit card debt and secured mortgage debt, examining outcomes including health satisfaction, mental health (as measured by the SF-36 Mental Component Score (MCS)), obesity, and repayment stress. In individual fixed-effects models, each 10-percentage-point increase in the credit-card debt-to-income ratio is associated with a 0.028-point decline in health satisfaction and a 0.402-point decline in the MCS; mortgage-debt estimates are small and inconsistent. Reporting mortgage-repayment stress corresponds to a 0.081-point lower health satisfaction and a 2.884-point lower MCS. Evidence for obesity is weak in the fixed-effects models. Overall, the findings suggest that the type of debt and the stress it generates are more significant for health than the total amount borrowed.